(untitled) (Cadernos de Sociomuseologia, 2017)
In this article we present the research project underway in the PhD in Museology by ULHT, where it is proposed to map the archaeological sites of Setúbal, identifying the sites with relevance to the community (s) and with which they identify, characterizing the memories associated to the archaeological sites with connection to the communities and to analyze the relation that the communities establish with these sites. Along with the relationship established between the community and the archaeological site, the methods of dissemination and communication of archeology as a science and as a practice are analyzed, proposing terms such as Clandestine Archeology and Trench Archeology. Keywords: Memory; Community; Identity; Archaeological practices; Archeology of trench